MORPHOLOGICAL CHARACTERISTICS OF SUPERIOR PURPLE AND LOCAL RED CORNS - Maemunah Maemunah; Sakka Samudin; Mustakim Mustakim (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
Before crossing plants, it's critical to understand their morphological characteristics. Differences in plant morphological features distinguish the advantages of each plant. The objective of this study was to determine the morphological characteristics of superior purple and local red corn cultivated at the height of 22 meters above sea level, as well as their adaptability. Kalukubula Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi was the site of this study. The research took place between October 2020 and February 2021. A Randomized Block Design was used in this investigation, with two corn kinds as treatments: The experiment was repeated 16 times with purple superior corn and red corn, yielding 32 experimental units. The quantitative data was examined using ovarian analysis (ANOVA) followed by a 5% Tukey HSD test to assess the difference between the two corns. Plant height, number of leaves, leaf length, stem diameter, age of male flower appearance, harvest age, fruit diameter with husk, length of cob, number of seeds per fruit, the weight of kernel per fruit, and dry kernels production of tons/ha were all found to have a higher growth rate than purple corn kernels. The qualitative characters of superior purple corn kernels include: leaf veins and leaf bases are purple, stems are purplish-green, female flowers are white with anger, the husk is purplish-green, and kernels are purple-black. Local red corn include white leaf veins, light green leaf bases, purple stems, light green female flowers, purple husk, and red kernels.